The The Impact of the Job Creation Law on Spatial Planning Policy: Challenges and Opportunities - Utari Dewi Fatimah; Robi Assadul Bahri (Warmadewa Press, 2025)
The birth of the Job Creation Law brings significant changes to spatial planning policies in Indonesia, with deregulation aimed at increasing investment and permitting efficiency. However, these changes also raise concerns regarding environmental sustainability and effective spatial governance. This research aims to evaluate the impact of the Job Creation Law on spatial planning policies in Indonesia and offer policy recommendations that can balance investment interests with environmental sustainability needs. This research use normative legal research employs a conceptual and statutory approach. Data were collected through literature studies that included legislation and scientific literature and then analyzed qualitatively from a legal perspective. The research results indicate that the Job Creation Law creates opportunities for increased investment but poses significant challenges in terms of oversight, coordination, and environmental preservation. Deregulation that facilitates land permits risks causing environmental degradation and conflicts of interest, especially in areas with high ecological vulnerability. The implications of this research are the importance of developing more adaptive spatial planning policies, strengthening implementation capacity at the regional level, and improving coordination between the central and regional governments. In addition, community involvement needs to be enhanced to support accountability and sustainability in spatial planning during this era of regulatory changes.